Cultivar Selection in Tomato and Pepper Production - Gene McAvoy (EDIS, 2008)
IPM-202, a 3-page illustrated fact sheet by G. McAvoy, was compiled from material in “Chapter 2 - Tomato and Pepper Production” of the Grower's IPM Guide for Florida Tomato and Pepper Production. It provides guidelines for selecting varieties suited to a grower's farming operation for greatest profitability. Published by the UF Department of Entomology and Nematology, December 2007.